2021
DOI: 10.2478/aoas-2020-0077
|View full text |Cite
|
Sign up to set email alerts
|

Effects of chestnut tannins supplementation of prepartum moderate yielding dairy cows on metabolic health, antioxidant and colostrum indices

Abstract: This study investigated the effects of dietary supplementation with chestnut tannins (CNT) on metabolic and antioxidant status of prepartum cows along with their colostrum quality. Pregnant multiparous Holstein cows were paired according to parity and body condition score, and assigned either to a diet supplemented with 20 g/d of commercially available product containing chestnut tannins (CNT, n=20) or to an unsupplemented control diet (CON, n=20) for the last 25±2 d of pregnancy. Serum metabolite, insulin and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 43 publications
0
6
0
Order By: Relevance
“…Numerous physiological processes involved in animal growth result in the generation of free radicals, which, if not scavenged, may initiate oxidative stress [ 52 ]. Previous studies have reported the antioxidant capacity of tannins [ 2 , 53 ]. However, the biological processes underlying how tannins respond to antioxidant enzymes are not fully understood.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous physiological processes involved in animal growth result in the generation of free radicals, which, if not scavenged, may initiate oxidative stress [ 52 ]. Previous studies have reported the antioxidant capacity of tannins [ 2 , 53 ]. However, the biological processes underlying how tannins respond to antioxidant enzymes are not fully understood.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, we used a model of dietary supplementation with chestnut tannins to gain information on antioxidant indices such as SOD, GPx, and GSH and thyroid hormone levels in prepartum dairy cows. Previous studies defined the antioxidant and free radical scavenging potential of chestnut tannins [ 7 , 8 , 9 ]. Our results show that CNT cows have higher activities of SOD and GPx as well as total antioxidants and lower TBARS levels than CON cows, indicating the ability of the antioxidant defence system and/or lower level of oxidative stress in CNT cows.…”
Section: Discussionmentioning
confidence: 99%
“…The ability of tannins to improve feed efficiency and antioxidant status in dairy cows is well known, and they have often been supplemented in the diet of dairy cows [ 7 , 8 , 9 ]. Tannins have also been suggested as effective alternatives to antibiotics to suppress rumen methanogenesis through their antimicrobial activity [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Conversely, the potential role of supplemental tannins on humoral response in ruminants is sparsely explored and requires further investigations. Recently, Prodanović et al [ 77 ] observed higher IgG levels in the colostrum of cows supplemented with chestnut tannins extract compared to control groups. These authors hypothesized that dietary tannins, depressing the protein degradation rate in the rumen, increased the protein portion available in the intestine, thus promoting colostrum quality and colostral IgG levels.…”
Section: Discussionmentioning
confidence: 99%